2017
DOI: 10.29356/jmcs.v61i2.263
|View full text |Cite
|
Sign up to set email alerts
|

A pyrazine amide – 4-aminoquinoline hybrid and its rhodium and iridium pentamethylcyclopentadienyl complexes; evaluation of anti-mycobacterial and anti-plasmodial activities

Abstract: The synthesis and characterization of N-(2-((7-chloroquinolin-4-yl)amino)ethyl)pyrazine-2-carboxamide (<strong>L</strong>), an aminoquinoline – pyrazinamide hybrid, and the complexes (N-(2-((7-chloroquinolin-4-yl)amino)ethyl)pyrazine-2-carboxamide)(cyclopentadienyl) chlorido-rhodium or iridium hexafluorophosphate ([M(<strong>L</strong>)(Cp*)Cl] PF<sub>6</sub>; M = Rh, Ir) and the corresponding chlorido salts ([M(<strong>L</strong>)(Cp*) Cl]Cl; M = Rh, Ir) are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Mechanistic studies further suggested that the complexes acted via the inhibition of hemozoin synthesis, which is a pathway unique to the malaria parasite and a crucial detoxification mechanism. [24,25].…”
Section: Quinoline-salicylaldiminato/picolamine/imidazole Ligandsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanistic studies further suggested that the complexes acted via the inhibition of hemozoin synthesis, which is a pathway unique to the malaria parasite and a crucial detoxification mechanism. [24,25].…”
Section: Quinoline-salicylaldiminato/picolamine/imidazole Ligandsmentioning
confidence: 99%
“…Recently, the research group of Smith reported a series of neutral, cyclometallated Ir(III)Cp* complexes (25), based on the 2-phenylbenzimidazole scaffold (24), showing in vitro antiplasmodial activity against NF54 and K1 strains of P. falciparum ( Figure 6) [31]. The synthesized complexes displayed activities in the low micromolar range against the tested strains.…”
Section: Benzimidazole (Hybrid) Ligandsmentioning
confidence: 99%
See 3 more Smart Citations